If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6s + 22 = 82 Reorder the terms: 22 + 6s = 82 Solving 22 + 6s = 82 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + 6s = 82 + -22 Combine like terms: 22 + -22 = 0 0 + 6s = 82 + -22 6s = 82 + -22 Combine like terms: 82 + -22 = 60 6s = 60 Divide each side by '6'. s = 10 Simplifying s = 10
| x/6-2=14 | | 2+7(3.8-1.4)= | | -7x+5y-6y+8x= | | -50x^9/25x^6 | | 3a-(2a-5)=30 | | 3x+3=15+0x | | x^2-3x-15= | | -1-7x=3+2x | | a^3+2=11 | | 48-5x= | | x^3-x^2-x-4=0 | | s^3-s^2-s-4=0 | | 5t^2+9=234 | | 3t+9=t+13 | | 1+3(2x-7)=8-4(3x+1) | | 5(4+m)-3(3m-1)=-9 | | 3a+10=3a-4 | | 9ab^2+27a^3-27a^2b-b^3+c^3=0 | | 2z+6=36 | | 5p+9=4p+8 | | -2(6z-3)+13(z-7)=-81-9 | | 25x=4x^(1/3) | | 9s-8(s-10)+3=84 | | 3x+8y=59 | | -3(s-2)+4s=-11-2 | | 7(s-2)+4s=-11-2 | | 5(3x+8)+5x=5(2d+10)-36 | | 4(4b+6)=3(2b-18) | | y=150-s | | 4(3y-1)-2y=56 | | 3(2n-6)=4m-10 | | 9(m-1/3)=9 |